Evaluation of different concentrations of rectified ethanol in the production of the “Bioaroma” ethyl acetate and single cell protein from Candida utilis var. major C.E.C.T. 1430 - León, Carlos (2010)
The present research was carried out with the purpose to evaluate the different concentrations of rectified ethanol in the production of “bioaroma” ethyl acetate and single cell protein from Candida utilis var.major for it a stirred – tank reactor of 16 cm of height with turbine Rushton was built. The preparation of the inoculum was carried out starting from Candida utilis var. major C.E.C.T. 1430. The broth of culture was formulated starting from rectified ethanol dilutions from 10 to 35 g/L each 5 units. The bioprocess was carried out at 25ºC to pH 4.5 – 5.5 and during a time of 60 hours. It was found that the biomass productivity increase progressively from 4.82 to 7.90 g/L and from 0.082 a 0.108 g/L-h) respectively. Such as increase the rectified ethanol concentration (g/L) the production and the yield was down. The yield acetate ethyl was top to concentrations of 15 g/L of rectified ethanol (5.7%) and smallest to concentrations of 35 (g/L) of rectified ethanol (1.97%). Finally, the increase of rectified ethanol concentrations does not influence increasing the production of acetate ethyl and the single cell protein Candida utilis var. major.